Can Sales Revenue Mediate the Relationship Between Market Share and Food Waste Management Practices at Restaurants in Banyumas? - Faizah, Putri Nur; Romadlon, Fauzan; Winati, Famila Dwi; Wan Ahmad, Wan Nurul Karimah (Journal of Marketing Innovation (JMI), 2024)
Indonesia, with its substantial population, faces a critical issue with food waste. The country's high food waste generation is concerning and necessitates action for sustainable development. Banyumas, a region experiencing a rise in restaurants and significant food expenditure, is particularly affected. In 2022, the restaurant sector in Banyumas emerged as the second-largest business sector, underscoring its significance and the need for focused attention. To effectively address food waste, it is crucial for restaurants to understand the interplay between sales revenue, market share, and waste management practices. This research explores the relationship between these factors within Banyumas' restaurant industry. Utilizing a quantitative approach, the study surveyed 102 restaurants in Banyumas Regency and employed SEM-PLS for model testing. Findings indicate that higher sales revenue positively influences food waste management practices, suggesting that increased income enables restaurants to better implement waste management strategies. This insight highlights the need for government efforts to enhance knowledge and coordination regarding restaurant food waste management